Exploring Neurocognitive Factors Underlying Autism and Hyperphagia in Prader-Willi Syndrome - Feighan, Sarah-Marie (Trinity College Dublin. School of Medicine. Discipline of Psychiatry, 2024)
Background: Prader-Willi Syndrome (PWS) is a rare complex multisystem genetic disorder recognised as the most common genetic cause of life-threatening obesity in humans (Butler, 1996). The PWS genotype gives rise to a complex behavioural phenotype. Autism symptoms and hyperphagia, a feeling of extreme hunger, are prevalent and impairing features of the PWS behavioural phenotype. Understanding the neurocognitive nature of autism behaviours in people with PWS will clarify if autism behaviours are related to social cognitive impairments, which will be imperative for understanding if ASD therapies may be suitable for some people with PWS. Identifying neurocognitive factors underlying hyperphagia will determine if eye tracking can be used as an objective measure of hyperphagia. A lack of objective measures of hyperphagia is currently a significant barrier to evaluating potentially life-altering drug therapies for hyperphagia. Aims and structures of thesis: The primary objective of this thesis was to enhance comprehension of PWS by profiling the mental health and behaviour needs of individuals with PWS and contributing critical knowledge to understanding neurocognitive factors underlying autism behaviours and hyperphagia using eye tracking technology. Chapter 1 introduces the PWS behavioural phenotype and discusses findings in the literature supporting the exploration of neurocognitive factors in neurodevelopmental conditions using eye tracking methodology. The thesis aims, and hypotheses are introduced. Chapter 2 describes the different methodologies used to investigate each chapter's hypotheses. Chapter 3 describes the results from a national survey carried out with PWS parents/caregivers and summarises findings in relation to psychiatric comorbidities, behaviours of concern, service needs and the impact of caring in families of an individual with PWS. Chapter 4 presents a study investigating social cognition in PWS by examining preferences for social stimuli and their relationship with autism and social functioning using a well-established passive viewing eye tracking paradigm, the face pop task. Chapter 5 describes the Food Attentional Bias (FAB) task, an innovative eye tracking paradigm, to explore variations in visual attention towards food stimuli as a potential measure of hyperphagia. This chapter develops and tests the task in a health-weight cohort. Chapter 6 describes the participatory approach used to conduct focus groups with PWS stakeholders to determine what adaptations would be required to implement the FAB task protocol in PWS. Chapter 7 discusses the results of implementing the adapted FAB task protocol from Chapter 6 in individuals with PWS and an age and gender-matched neurotypical comparison group. Finally, Chapter 8 presents a discussion of the findings. Results: The survey results from Chapter 3 revealed a high prevalence of psychiatric disorders and behaviour challenges in PWS, highlighting the complex mental health and behavioural needs of individuals with PWS. Caregivers expressed that their employment, family relationships, and emotional well-being were significantly affected, highlighting the notable impact experienced by them. The investigation of social cognition in Chapter 4 revealed that PWS participants looked at social stimuli relatively more than the comparison group as measured by the proportion of fixations to face stimuli. However, higher levels of autism symptoms in the PWS group were associated with reduced sustained attention to faces, which has also been reported in autism cohorts. These findings suggest that endogenous deployment of attention to social stimuli may be reduced in individuals with co-occurring PWS and autism. In Chapter 5, an objective measure of satiety was investigated using an eye tracking task modified from the 'face pop' task described in Chapter 4. The FAB task measured interest in food stimuli across two meal conditions, pre-and postmeal. Healthy-weight participants showed a clear reduction in attention to food stimuli in the postmeal condition, as evidenced by shorter durations and fewer fixations on food stimuli. This finding suggested that changes in attention to food stimuli from premeal to postmeal may be a marker of satiety in typically developing populations. In Chapter 6, the main theme to emerge from the focus groups with PWS stakeholders was the importance of communication and cooperation between researchers and participants' parents/caregivers when scheduling and organising the PWS research visit. Key adaptations were made to the protocol concerning this theme, such as the design of the premeal and postmeal study condition, the standardised meal approach taken, and the behavioural questionnaires used. In Chapter 7, the adapted FAB task protocol was implemented in PWS and showed that participants with PWS did not display a significant decrease in the number and duration of fixations on food stimuli in the post-meal condition. This differed from the comparison group, which showed reduced visual attention to food stimuli, similar to the healthy-weight group in Chapter 5. This outcome validated the primary objective of the FAB task protocol, showing that participants with PWS maintained their interest in food stimuli even after eating. The absence of reduced visual attention to food stimuli in PWS may reflect an atypical satiety response, a critical aspect of hyperphagia. Therefore the FAB task protocol has potential as a neurocognitive marker of hyperphagia and warrants further investigation. Conclusion: The results from this work provide novel insights into the neurocognitive nature of autism behaviours and hyperphagia in PWS. An improved understanding of social cognitive factors in PWS can inform treatment approaches for ASD symptoms and social functioning in PWS. Further investigation of visual attention to food stimuli has the potential as an objective marker of hyperphagia in PWS that could be used to monitor the treatment effectiveness of novel drug therapies.
APPROVED
Keywords: Hyperphagia; Eye tracking; Prader-Willi Syndrome; Autism; Social Cognition